Pentingnya Pelatihan Kompetensi Guru dalam Menghadapi Tantangan Pendidikan Masa Kini - Fitriawati (Yayasan Darussalam Bengkulu, 2024)
This study aims to examine the importance of teacher competency training in facing today's educational challenges, which are increasingly complex due to technological advances, curriculum changes, and diverse student needs. The research method used is quantitative, with a survey approach involving 200 elementary school teachers in several areas. Data were collected through a questionnaire designed to measure teachers' understanding of educational challenges, their skill levels, and relevant training needs. Data analysis was carried out using descriptive and inferential statistics to identify the relationship between competency training and teacher readiness to overcome these challenges. The results of the study showed that teachers who regularly participate in competency training have a better level of understanding of educational challenges and show higher readiness in implementing innovative teaching methods. These findings emphasize the need to develop sustainable and relevant training programs to improve teacher competence. With the right training, it is hoped that teachers can be better prepared to face the dynamics of education in the modern era and have a positive impact on the quality of education in elementary schools.